The implementation of the High School Reform in the State of Parana: the advancement of neoliberal policies and attacks to the Field Education (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2023)
This paper aims to analyze the advancement of neoliberal policies in Brazil, the High School Reform (Law no. 13,415/2017) and its implementation in the state of Paraná, Brazil, emphasizing its impact on public education and Field Education. It is bibliographic and documentary research, having as theoretical reference the dialectical and historical materialistic method. The High School Reform was guided by neoliberal policies and entrepreneurial groups, it serves the capital and market demands, and attacks directly the perspective of human education and emancipation. It is inferred that the Field Education project is not the result of educational reforms, but rather as the outcome of struggle and achievements of the field populations in the context of the fights for the land that originated public policies. In the historical fights and constructions of the Field Education emancipatory project reside the possibility of resistance to and confrontation with the education neoliberal project.Keywords: Neoliberal policies. High School Reform. Field Education.